THE EFFECT OF INCOME, CAREER DEVELOPMENT, AND LOCATION OF DUTY PLACE ON CIVIL SERVANT ENTRY MUTATION IN GOVERNMENT AGENCIES EAST LUWU REGENCY - Martini; Antang; Muammar Khaddapi; Safruddin, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study aims to analyze the influence of income, career development, and duty location on civil servant entry mutations in East Luwu Regency government agencies. The research conducted is explanatory research using a quantitative approach. This research was carried out at the Office of the East Luwu Regency Human Resources and Development Agency (BKPSDM). Data was obtained based on the List of Requests for Mutation of Civil Servants (PNS) entering the East Luwu Regency Government from 2022 to 2024 totaling 71 people. Data was collected through questionnaires that had been tested for validity and reliability. Data analysis to test the hypothesis using the variation-based Structural Equation Model (VB SEM). Data processing using the help of the Smart PLS application 3.2.9. The results of the study show that income, career development, and location of a significant effect on the mutation of civil servants in the East Luwu Regency Government. Effective employee management to prevent mutations is a crucial aspect in human resource management. Transfers, or the transfer of employees either to other positions within the organization (internal mutations) or to other organizations (external mutations), can have a significant impact on operational stability, team morale, and recruitment and training costs. Therefore, an employee management strategy designed to retain a quality workforce is essential to maintain the efficiency and long-term success of the organization.